Endoscopic control after retroperitoneal pancreas transplantation with a Roux-en-Y duodenojejunostomy for exocrine drainage - N. S. Zhuravel; A. G. Balkarov; R. V. Storozhev; Yu. A. Anisimov; A. S. Kondrashkin; D. V. Lonshakov; N. V. Shmarina (Трансплантология (Москва))
Background. Simultaneous pancreas and kidney transplantation is a gold standard in the treatment of diabetes mellitus complicated by stage 5 chronic kidney disease as a result of diabetic nephropathy. One of the main problems of clinical pancreas transplantation is the pancreas graft exocrine drainage. In order to preserve the advantages of the retroperitoneal graft location and avoid the main disadvantage of duodenal drainage, namely, fatal complications potentially arising in case of necessary graft removal, we have proposed a modified method of retroperitoneal pancreatic transplantation with exocrine drainage via a modified Roux-en-Y duodenojejunostomy. It reduces the number of severe surgical complications and increases the recipient survival rate. When this method was used in previous years, it was not possible to assess the condition of donor duodenum mucosa and interintestinal anastomoses.Objective. To demonstrate the possibility of endoscopic assessment of interintestinal anastomoses when performing retroperitoneal pancreas transplantation with small intestine drainage of exocrine secretions.Results. The article presents the initial experience of endoscopic assessment of the interintestinal anastomoses and the mucous membrane of the donor duodenum after retroperitoneal pancreas transplantation with exocrine drainage via a Roux-en-Y duodenojejunostomy.Conclusion. The presented case demonstrates the feasibility of diagnostic endoscopic interventions when performing retroperitoneal pancreas transplantation with small intestine drainage of pancreatic secretions.